Thermal annealing effect on β‐Ga2O3 thin film solar blind photodetector heteroepitaxially grown on sapphire substrate. Issue 8 (9th May 2017) - Rafique, Subrina; Han, Lu; Zhao, Hongping
Abstract : This paper presents the effect of thermal annealing on β‐Ga2 O3 thin film solar‐blind (SB) photodetector (PD) synthesized on c‐plane sapphire substrates by a low pressure chemical vapor deposition (LPCVD). The thin films were synthesized using high purity gallium (Ga) and oxygen (O2 ) as source precursors. The annealing was performed ex situ the under the oxygen atmosphere, which helped to reduce oxygen or oxygen‐related vacancies in the thin film. Metal/semiconductor/metal (MSM) type photodetectors were fabricated using both the as‐grown and annealed films. The PDs fabricated on the annealed films had lower dark current, higher photoresponse and improved rejection ratio ( R 250 / R 370 and R 250 / R 405 ) compared to the ones fabricated on the as‐grown films. These improved PD performances are due to the significant reduction of the photo‐generated carriers trapped by oxygen or oxygen‐related vacancies.